2018
DOI: 10.1186/s12917-018-1576-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor (VEGF) in equine sarcoid

Abstract: BackgroundSarcoids are the mostcommon skin tumors in horses, characterized by rare regression, invasiveness and high recurrence following surgical intervention and Delta Papillomaviruses are widely recognized as the causative agents of the disease. In order to gain new insights into equine sarcoid development, we have evaluated, in 25 equine sarcoids, by immunohistochemistry and western blotting analysis, the expression levels of VEGF, Ki67 and bcl-2. Moreover, we have measured microvessel density and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…The rank correlation analysis showed that the percentage of HIF-1α positive cells was positively correlated with the percentage of VEGF positive cells found during a previous study by our group (r = 0.60 p < 0.01) [27].…”
Section: Statistical Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…The rank correlation analysis showed that the percentage of HIF-1α positive cells was positively correlated with the percentage of VEGF positive cells found during a previous study by our group (r = 0.60 p < 0.01) [27].…”
Section: Statistical Resultssupporting
confidence: 69%
“…The examined sarcoids (n = 35) showed the classic histological features of the lesion: epidermal hyperplasia with rete pegs; hyperkeratosis; proliferation of neoplastic fibroblast in the dermal layer, oriented in a 'picket fence' perpendicular to the basilar epidermal layer; exuberant extracellular matrix; presence of many small vessels irregular in shape [26,27].…”
Section: Histological Featuresmentioning
confidence: 99%
See 3 more Smart Citations